PERKEMBANGAN PESERTA DIDIK PERSPEKTIF NATIVISME, EMPIRISME, NATURALISME, KONGVERGENSI - Syahril, SYAHRIL (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2016)
Abstract: The students are the human resources that have a high potention to be developed through educational process. In the development process, some experts have many different perceptions towards the determinat factors of the development like nativism, empirism, naturalism, and convergence. In spite of the difference perspective of the different schools towards the determinat factors of the development, it cannot be denied that the teachers have a crucial role to assess the students’ potenstion development. Kata Kunci: Perkembangan Peserta Dididk, Nativisme, Naturalism dan Kongvergensi